Computer Based Examination: The Need of the Time at DUHS - Ata Ur Rahman; Syed Moyn Aly (Journal of the Dow University of Health Sciences, 2012)
Dow University of Health Sciences (DUHS) Karachi is one of the budding institutions moving with high pace. There is a gross increase in number of students and number of assessment sessions held each year. Latest module based integrated system is further increasing the work load. This involves the full faculty in terms of time and energy, which are of great value and needs priority in utilization. The consumption of time leads to disturbance in education process also.